The effects of melatonin in the treatment of acute brachial plexus compression injury in rats - Li, Xigong; Fu, Jing; Zhou, Haiying; Dong, Yanzhao; Alhaskawi, Ahmad; Wang, Zewei; Lai, Jingtian; Yao, Chengjun; Ezzi, Sohaib Hasan Abdullah; Kota, Vishnu Goutham; Abdulla, Mohamed Hasan Abdulla Hasan; Guan, Ming; et al. (Frontiers in Neurology, 2023)
The aim of this study was to evaluate the effects of melatonin in the treatment of acute brachial plexus compression injury in rats using histopathological, histomorphometric, immunohistochemical and electrophysiological methods. Twenty-four adult male Sprague Dawley rats were randomly allocated into three groups: sham, melatonin and vehicle groups. The brachial plexus compression injury model was performed by a vascular clamp. Melatonin group received intraperitoneal injection of melatonin at doses of 10 mg/kg for 21 days after crush injury. The compound muscle action potential (CAMP) conduction velocity and amplitude in the regenerated nerve, nerve histomorphometry, and levels of myelin protein zero (P0) protein at the crush site were assessed. The melatonin group had significantly increased CMAP conduction velocity, enhanced myelin sheath thickness and increased P0 protein levels compared with the vehicle group. Our results suggest that melatonin effectively promotes nerve regeneration and improves the function of damaged nerves. Melatonin treatment is a promising strategy for the treatment of acute brachial plexus compression injury.